The Effect of Learning Style with Synchronous and Asynchronous Educational Activities in Developing Social Skills and Systemic Thinking in the Light of the 21st Century Skills among Female Students of Al-Balqa Applied University - Smadi, Safa’a Ahmad; Lsoud, Lubna; Bani Attah, Jawaher; Danaa, Hana Mustafa Amin; Humaidat , Mahmoud Ahmed (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to show the impact of education form through synchronous activities and asynchronous activities on enhancing social skills and systems thinking for students from Al-Balqa Applied University. Methods: The study used the semi-experimental approach. To achieve the objectives of the study, two tools were prepared: a scale of social skills and a test of systems thinking. The validity and stability of both tools were verified. The study sample consisted of (42) female students distributed to the two experimental groups. The first group of learning style with synchronous activities included 22 students and the second group of learning style with asynchronous activities included 20 students. Both groups were at the level of Princess Alia College, Al-Balqa Applied University, and they specialized in home economics. The first experimental group then implemented the learning form with synchronous activities, while the second experimental group implemented the learning form with asynchronous activities. Results: The results of the study showed statistically significant differences (α=0.05) in social skills and systems thinking between both study groups due to the impact of the learning form and were in favour of the learning group's synchronous activities. Conclusions: The study recommended including synchronous educational activities in teacher preparation and training programs and computerizing them into interactive applicable programs.